Does the current sustainability reporting of the software company meet the requirements of European Sustainability Reporting Standards : a case study - Laine, Venla (2024)
The environment in which organizations operate is changing and with sustainability reporting they can transparently address the economic, environmental, social, and governance impacts of the company’s processes. The importance of corporate social responsibility is increasing internationally, and European Union has responded to this with a new regulation. The European Sustainability Reporting Standard (ESRS) defines a standardized framework for evaluating material negative and positive impacts as well as risk and opportunities regarding the undertaking’s sustainability. The purpose of this study was to analyze the current sustainability reporting model of software company Pinja Group Oy and define if it meets the requirements of European Sustainability Reporting Standards. To evaluate the company’s current sustainability report, Global Reporting Initiative (GRI) indicators and metrics were compared to the new ESRS requirements. The comparability with ESRS was analyzed with gathering both qualitative and quantitative data regarding sustainability reporting frameworks from EU legislation, global frameworks, and from the company data. The sustainability reporting of Pinja Group was evaluated to meet the minimum ESRS requirements of financial reporting. The current GRI-based reporting met climate change, own workforce, and consumer as well as business conduct ESRS requirements which were material. To present an extensive picture of their sustainability impacts in the future, the organization should conduct double materiality assessment as a first step to meet the requirements of ESRS.